تأثير تحرير التجارة الخارجية على اقتصاديات الدول النامية في ظل التطورات الاقتصادية الراهنة - دراسة حالة الجزائر- - مصراوي منيرة (My University, 2017)
This thesis sheds light on the reality of trade liberalization and its effects in developing countries with an emphasis on the Algerian situation. Then, after tacking the theoretical aspect of the international trade and the strategy of development, we tried to explain the relationship between the two concepts. After Algeria liberalized its trade and embraced the international trade, we tried to demonstrate the impact of this liberalization on economic factors. The conclusion we reached in this study is that the international trade in developing countries didn’t play its central role in boosting the progress of their economy especially in our case study “ Algeria”
Keywords: liberalization of international trade, world trade organization ( W.T.O), strategy of development in developing countries.